Ce diaporama a bien été signalé.
Le téléchargement de votre SlideShare est en cours. ×

# Linear Algebra C A (C^T) D A (C^T) C - C (A^T) Tryed solving it for.docx

Publicité
Publicité
Publicité
Publicité
Publicité
Publicité
Publicité
Publicité
Publicité
Publicité
Publicité  Chargement dans…3
×

## Consultez-les par la suite

1 sur 2 Publicité

# Linear Algebra C A (C^T) D A (C^T) C - C (A^T) Tryed solving it for.docx

Linear Algebra

C A (C^T) D A (C^T) C = C (A^T)

Tryed solving it for days, it\'s so hard, thank you very much to whoever manages to solve it, please show your work too, thank you.
Solution
CA(C^(T))*DA(C^(T))*C=C(A^(T))

Multiply AC by AD to get A^(2)CD.
A^(2)CD(C^(T))(C^(T))*C=C(A^(T))

Multiply A^(2)CD by C to get A^(2)C^(2)D.
A^(2)C^(2)D(C^(T))(C^(T))=C(A^(T))

Multiply C^(T) by C^(T) to get C^(2T).
A^(2)C^(2)D(C^(2T))=C(A^(T))

Multiply A^(2)C^(2)D by each term inside the parentheses.
A^(2)C^(2T+2)D=C(A^(T))

Divide each term in the equation by A^(2)C^(2T+2).
(A^(2)C^(2T+2)D)/(A^(2)C^(2T+2))=(C(A^(T)))/(A^(2)C^(2T+2))

Simplify the left-hand side of the equation by canceling the common factors.
D=(C(A^(T)))/(A^(2)C^(2T+2))

Simplify the right-hand side of the equation by simplifying each term.
D=A^(T-2)C^(-2T-1)
.

Linear Algebra

C A (C^T) D A (C^T) C = C (A^T)

Tryed solving it for days, it\'s so hard, thank you very much to whoever manages to solve it, please show your work too, thank you.
Solution
CA(C^(T))*DA(C^(T))*C=C(A^(T))

Multiply AC by AD to get A^(2)CD.
A^(2)CD(C^(T))(C^(T))*C=C(A^(T))

Multiply A^(2)CD by C to get A^(2)C^(2)D.
A^(2)C^(2)D(C^(T))(C^(T))=C(A^(T))

Multiply C^(T) by C^(T) to get C^(2T).
A^(2)C^(2)D(C^(2T))=C(A^(T))

Multiply A^(2)C^(2)D by each term inside the parentheses.
A^(2)C^(2T+2)D=C(A^(T))

Divide each term in the equation by A^(2)C^(2T+2).
(A^(2)C^(2T+2)D)/(A^(2)C^(2T+2))=(C(A^(T)))/(A^(2)C^(2T+2))

Simplify the left-hand side of the equation by canceling the common factors.
D=(C(A^(T)))/(A^(2)C^(2T+2))

Simplify the right-hand side of the equation by simplifying each term.
D=A^(T-2)C^(-2T-1)
.

Publicité
Publicité

### Linear Algebra C A (C^T) D A (C^T) C - C (A^T) Tryed solving it for.docx

1. 1. Linear Algebra C A (C^T) D A (C^T) C = C (A^T) Tryed solving it for days, it's so hard, thank you very much to whoever manages to solve it, please show your work too, thank you. Solution CA(C^(T))*DA(C^(T))*C=C(A^(T)) Multiply AC by AD to get A^(2)CD. A^(2)CD(C^(T))(C^(T))*C=C(A^(T)) Multiply A^(2)CD by C to get A^(2)C^(2)D. A^(2)C^(2)D(C^(T))(C^(T))=C(A^(T)) Multiply C^(T) by C^(T) to get C^(2T). A^(2)C^(2)D(C^(2T))=C(A^(T)) Multiply A^(2)C^(2)D by each term inside the parentheses. A^(2)C^(2T+2)D=C(A^(T)) Divide each term in the equation by A^(2)C^(2T+2). (A^(2)C^(2T+2)D)/(A^(2)C^(2T+2))=(C(A^(T)))/(A^(2)C^(2T+2)) Simplify the left-hand side of the equation by canceling the common factors. D=(C(A^(T)))/(A^(2)C^(2T+2)) Simplify the right-hand side of the equation by simplifying each term. D=A^(T-2)C^(-2T-1)